Perceptions and engagement experiences of cultural landscapes among the Sebat Bête Gurage in Ethiopia: a dwelling and multifunctional landscape perspectives - Abinet Shiferaw; Mamo Hebo; Getachew Senishaw (Cogent Social Sciences)
This article investigates the Sebat Bête Gurage’s perceptions and engagement experiences with their cultural landscapes. Using phenomenology and landscape multifunctionality approaches, it examines the relationships between social groups and everyday landscapes as sites of dwelling, well-being, and interaction. The study utilised ethnographic in-depth interviews, focus group discussions and observations. The data was analysed qualitatively by generating themes and meanings from various data sources. Social groups such as children, youth, elderly, women, men, the disadvantaged, crafts, non-local residents and local government agents perceive and engage with landscapes based on their socio-economic and well-being associations. Non-Gurage local residents have positive perceptions and well-being associations, despite their socio-cultural backgrounds. Local government actors viewed village landscapes as public reserves for infrastructure and service expansions, despite the costs of prior landscape identities and provisions. Shared perceptions and engagement experiences exist in public landscapes, regardless of the socio-economic differences of social groups. Social groups viewed landscapes as ancestors’ gifts that stored values of man-environment interactions, memories, identities, and well-being associations. However, landscape dynamics due to intrusions, encroachments, and generation gaps regarding landscape values challenge social groups’ perceptions and landscape associations, leading to a decrease in landscape appreciation and well-being associations and a shift in perceptions. Henceforth, decision-making and interventions in village landscapes necessitate consultation of diverse interests, social demands, prior landscape provision, and long-standing landscape values as part of policy decisions in the case of micro-landscapes. An understanding of landscape dynamics among social groups is also needed to inform policy for micro-landscape decisions to balance conflicts of interests, diverse demands and ensuring landscape sustainability and multifunctionality.